Predictors of functional communication in people with aphasia after stroke - Fernandes, Adriana; Fraga-Maia, Helena; Maso, Iara; Matos, Isabela Guimarães; Gomes, Lene; Matos, Matheus; Santana, Andressa; Oliveira-Filho, Jamary; Jesus, Pedro Antônio de; Pinto, Elen Beatriz (Arquivos de Neuro-Psiquiatria, 2022)
Background Aphasia, the most common language disorder secondary to stroke, has been associated with increased mortality, longer hospitalization and rehabilitation times, worse performance in daily activities, increased financial burden, and short- and long-term complications. Aphasia can negatively impact functional communication skills, including social networks, social activities, relationships with other people and social support.Objective To evaluate patients with poststroke aphasia in their respective residences to investigate potential predictors of functional communication.Methods The prospective cohort included patients with poststroke aphasia aged 18 years or older who resided in the city of Salvador, Northeastern Brazil. Following discharge from the Stroke Unit (SU), the individuals themselves, or their guardians, were contacted by telephone to schedule a home visit no less than three months after discharge. At baseline, sociodemographic and clinical data were collected, in addition to the scores on the National Institutes of Health Stroke Scale (NIHSS) and modified Barthel Index (mBI). The American Speech-Language-Hearing Association Functional Assessment of Communication Skills for Adults (ASHA FACS) was applied at the patients' homes. Multivariate linear regression was employed using the total score on the ASHA FACS as the outcome of interest.Results A multivariate analysis of the associated factors identified using the linear regression revealed that only functional capacity (as assessed by the mBI) upon discharge from the SU remained as an independent predictor of functional communication performance (β = 0.042; 95% confidence interval [95%CI] = 0.013–0.071; p = 0.002).Conclusion The functional capacity to perform daily activities, evaluated upon discharge from a stroke unit, was identified as a potential predictor of functional communication performance, regardless of the time elapsed after the stroke.
Keywords: Stroke; Aphasia; Communication; Community Integration